Method for DNA Ploidy Analysis Along with Immunophenotyping for Rare Populations in a Sample using FxCycle Violet. Issue 1 (3rd April 2017) - Tembhare, Prashant; Badrinath, Yajamanam; Ghogale, Sitaram; Subramanian, Papagudi Ganesan
Abstract: The clinical use of flow cytometric DNA ploidy assay has been extended towards stratifying the risk of diseases, such as monoclonal gammopathies or B cell acute lymphoblastic leukemia, and to detect circulating tumor cells, both of which require detection of minute cell populations. This unit describes a protocol for determining DNA ploidy in fixed samples with simultaneous surface immunophenotyping. It is an easy method for simultaneous 6‐ to 8‐color immunophenotyping and DNA content analysis using FxCycle Violet (FCV; DAPI) dye. This protocol is a one‐step modification of routine multicolor immunophenotyping that includes surface staining followed by fixation and then DNA staining with FCV. It utilizes mature lymphocytes from the sample as an internal control for determination of DNA index. It is a sensitive method that allows DNA‐ploidy determination and cell cycle analysis in a rare tumor population as low as 100 events, as well as DNA ploidy determination in various subsets of hematopoietic cells in the same sample based on their immunophenotype. © 2017 by John Wiley & Sons, Inc.